Die Bildpublizistik der Französischen Revolution - Herding, Klaus; Reichardt, Rolf (Suhrkamp, 1989)
Klaus Herding, Rolf Reichardt: "Die Bildpublizistik der Französischen Revolution". Suhrkamp Verlag, Frankfurt am Main 1989. 178 S., Abb., geb., 48,- DM